Huntingtin Aggregates in the Olfactory Bulb in Huntington’s Disease - Highet, Blake; Dieriks, Birger Victor; Murray, Helen C.; Faull, Richard L. M.; Curtis, Maurice A. (Frontiers in Aging Neuroscience, 2020)
Olfactory deficits are an early and prevalent non-motor symptom of Huntington’s Disease (HD). In other neurodegenerative diseases where olfactory deficits occur, such as Alzheimer’s and Parkinson’s Disease, pathological protein aggregates (tau, β-amyloid, α-synuclein) accumulate in the anterior olfactory nucleus (AON) of the olfactory bulb (OFB). Therefore, in this study we determined whether aggregates are also present in HD OFBs. 13 HD and five normal human OFBs were stained for mutant huntingtin (mHtt), tau, β-amyloid, TDP-43 and α-synuclein. Our results show that mHtt aggregates detected with 1F8 antibody are present within all HD OFBs and mHtt aggregate load in the OFB does not correlate with Vonsattel grading scores. The majority of the aggregates were located in the AON and in similar abundance in each anatomical segment of the AON. No mHtt aggregates were found in controls. 31% of HD cases also contained tau neurofibrillary tangles within the AON. This work demonstrates HD pathology in the OFB and indicates that disease specific protein aggregation in the AON is a common feature of neurodegenerative diseases that show olfactory deficits.